CFD-DEM Investigation on van der Waals Force in Gas-Solid Bubbling Fluidized Beds - Mahsa Okhovat (Journal of Chemical and Petroleum Engineering, 2018)
Effect of interparticle force on the hydrodynamics of gas-solid fluidized beds was investigated using the combined method of computational fluid dynamics and discrete element method (CFD-DEM). The cohesive force between particles was considered to follow the van der Waals equation form. The model was validated by experimental results from literature in terms of bed voidage distribution and Eulerian solid velocity field. The results revealed that the incorporated model can satisfactorily predict the hydrodynamics of the fluidized bed in the presence of interparticle forces. Effect of interparticle force on the bubble rise characteristics, such as bubble stability, bubble diameter and bubble velocity, was investigated. It was shown that the emulsion voidage increases with increasing the interparticle force in the bed and it can hold more gas inside its structure. In addition, by increasing the interparticle force, size of bubbles and rise velocity of bubbles increase while the average velocity of particles decreases.